Consider rights of all involved in reports of sexual harassment, assault. Issue 11 (March 2015) - Porter, Michael
<x xml:space="preserve">Abstract</x> Colleges and universities want to make their campuses safe learning environments for all students, but instances of sexual harassment and assault undermine that goal. In addition, recent enforcement efforts made by the Department of Education's Office for Civil Rights under Title IX reinforce the already existing incentive to address sexual assault and harassment, and Title IX compliance reduces legal exposure to complainants' claims.